2010
DOI: 10.2353/ajpath.2010.091166
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Estrogen Receptor 1 Enhances Cervical Cancer Invasion

Abstract: If left untreated, some cervical high-grade squamous intraepithelial lesions will progress to invasive squamous cell carcinoma (SCC), but the molecular events conferring invasive potential remain poorly defined. In prior work, we identified 48 genes that were downregulated in SCCs compared with high-grade squamous intraepithelial lesions and normal squamous epithelia. In this study, a functional screening strategy was used to identify which of these genes regulate cervical cancer cell invasion. Two independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
44
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 40 publications
5
44
0
Order By: Relevance
“…Squamous cell carcinoma is the most common invasive malignancy of the cervix, vagina, and vulva (34). Although much remains to be learned about the underlying molecular mechanisms, loss of ESR1 has been associated with squamous cell carcinoma progression and invasion (35). Although we showed dysregulated epithelial cell proliferation and differentiation in the K5-Esr1KO mouse vagina and found that prolonged estrogen exposure induced abnormal epithelial invagination into the stroma, cancerous lesions and indications of metastatic phenotypes (e.g., effects on basement membrane) were not observed.…”
Section: Discussionmentioning
confidence: 99%
“…Squamous cell carcinoma is the most common invasive malignancy of the cervix, vagina, and vulva (34). Although much remains to be learned about the underlying molecular mechanisms, loss of ESR1 has been associated with squamous cell carcinoma progression and invasion (35). Although we showed dysregulated epithelial cell proliferation and differentiation in the K5-Esr1KO mouse vagina and found that prolonged estrogen exposure induced abnormal epithelial invagination into the stroma, cancerous lesions and indications of metastatic phenotypes (e.g., effects on basement membrane) were not observed.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, these genes were induced exclusively in the tumor stroma of mouse origin but not in the mammary carcinomas of human origin (24). One of the most up-regulated genes was Paternally expressed gene 3 (Peg3), an imprinted putative tumor-suppressor gene frequently silenced by promoter hypermethylation and/or loss of heterozygosity (25)(26)(27)(28)(29)(30). Interestingly, Peg3 binds β-catenin and promotes 26S proteasomal degradation that is, surprisingly, independent of glycogen synthase kinase-3β GSK3β (31).…”
mentioning
confidence: 99%
“…While in cervix cancer cells, estrogen receptor type that more dominant is estrogen receptor-α. Decreased levels of estrogen receptor-α in cervical cancer cells can increase malignancy of cancer cells [28,29,30]. Thus, it can be presumed that there are other pathways exist in addition to the estrogen receptor-α and -β that can increase the activation of p38 in our study.…”
Section: Intensity Of Intracellular Phospho-p38mentioning
confidence: 83%